Impact of Acid Leaching on Upgrading Indigenous Low-grade Chromite ore for Iron and Steel Plant Development - Ayinla, K.; Baba, A. A.; Oyewumi-Musa, R. T.; Tripathy, B. C.; Anafi, G. A.; Dwari, R. K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Low-grade chromite concentrate from the Tunga Kaduka Benue trough region of north-eastern Nigeria is contaminated with iron and aluminium impurities. To transform it into useful material, such impuririties must be removed for it to be useful for the production of special steel and ferrochrome alloys. Consequently, in this study, a Nigerian chromite was treated by hydrochloric acid (HCl) solution. The influence of leaching duration, acid concentration, reaction temperature, and particle size on the extent of impurities dissolution was determined. From the results obtained, the dissolution of iron and aluminium increases with increasing leaching time, HCl concentration, reaction temperature, and decreasing particle size. Under these conditions, the highest recovery of iron and aluminium was obtained to be 95.54 and 82.51%, respectively. The dissolution kinetics of iron and aluminium was evaluated by shrinking core models. The finding reveals that diffusion through the fluid was the leaching kinetics rate-controlling step of iron and aluminium. The activation energy was found to be 25.33 kJ/mol for iron and 18.42 kJ/mol for aluminium. The residual samples at optimal conditions as analyzed by X-ray powder diffraction and scanning electron microscopy were found to